PENGARUH VARIABEL MAKRO EKONOMI TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2015-2019 - Feby Kinanda (Jurnal Manajemen dan Bisnis Jayakarta, 2021)
This study aims to analyze the effect of macroeconomic variables including the open unemployment rate, trade balance, inflation rate and the rupiah exchange rate against the dollar on Indonesian economic growth by using the ECM error correction model approach to see the long-term and short-term relationships that influence macro variables on economic growth. , in the long term the open unemployment rate variable, the trade balance, the inflation rate have a negative effect while the exchange rate has a positive effect, while in the short term the open unemployment rate, the inflation rate and the exchange rate have a negative effect while the trade balance has a positive effect. Keywords: Economic Growth, Open Unemployment Rate, Trade Balance, Inflation, Exchange Rate